Exploring the Cognitive Impact of Bilingualism: Challenges and Advantages of Dual Language Use - Zahirah M, Nur Fadilah; Meilani, Puja Renita; Suhardi, Nur Asfira (Journal of Language Learning and Assessment, 2025)
Purpose This study explores the lived experiences of bilingual individuals regarding the cognitive demands and advantages associated with the regular use of two or more languages, focusing particularly on the cognitive challenges of language switching and the cognitive benefits such as enhanced executive control and cognitive flexibility. Methodology A qualitative phenomenological approach was employed, utilizing semi-structured interviews with bilingual adults to capture their subjective perceptions of cognitive functioning in real-life language switching situations. The data were analyzed using thematic analysis. Results/Findings Thematic analysis revealed a balance between cognitive load—such as mental effort and interference—and cognitive benefits including improved problem-solving and attentional control among bilingual individuals. Implications These findings contribute to a comprehensive understanding of bilingual cognition and have important implications for educational practices and language policy that aim to optimize cognitive and communicative outcomes for bilingual individuals.